Intraoperative complications after total laparoscopic hysterectomy: a retrospective study in training institute - Patel, Richa; Moray, Arun (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Hysterectomy is a common gynecological surgery performed in premenopausal and menopausal age group. Different types of approaches are there with their advantages and disadvantages, it is mainly indicated for noncancerous conditions. Till today three different surgical approaches to hysterectomy are available: vaginal, abdominal and laparoscopic. TLH has been reported to result in shorter procedure durations, lower blood losses, and shorter hospital stays. Methods: This is a retrospective case study, was carried out over a 5-year period in a tertiary care institute. Study done on patients attending gynecology OPD at our tertiary care institute during the period since September 2013 to September 2018. Results: In present study out of 646 endoscopic hysterectomies in last five years authors studied 420 Total Laparoscopic Hysterectomies. Conversion to open surgery rate was 0.3%. Mean age was 49.26 years (SD-9.53), Performed for various indications with various BMI patients. Mean surgical duration was 116.55 minutes with SD 26.27. Major complication rate was 2.85% with 2 cases of bowel injuries and 3 cases of urological injuries. Conclusions: Total laparoscopic hysterectomy appears safe and effective approach for variety of indications with minimal morbidity. Beneficial for all age group all nulliparous /multiparous patients as well as obese patients. With the knowledge of all complication and its prevention, maximum surgeons can give benefit of advantages of total laparoscopic hysterectomy to all women. More and more randomized clinical trials will motivate surgeons for this approach.